The mechanism of low molecular weight fucoidan-incorporated nanofiber scaffolds inhibiting oral leukoplakia via SR-A/Wnt signal axis - Xu, Ming; Sun, Yu; Cong, Beibei; Zhang, Xiaopei; Li, Zhenfeng; Liu, Yingnan; Geng, Lihua; Qin, Qi; Wu, Yingtao; Gao, Meihua; Wang, Wanchun; Wang, Yuanfei; et al. (Frontiers in Pharmacology, 2024)
Oral leukoplakia (OLK) is the most common oral precancerous lesion, and 3-17% of OLK patients progress to oral squamous cell carcinoma. OLK is susceptible to recurrence and has no effective treatment. However, conventional drugs have significant side effects. However, conventional drugs have significant side effects and limitations. Therefore, it is important to identify drugs that target OLK. In this study, scavenger receptor A (SR-A) was found to be abnormally highly expressed in the oral mucosal epithelial cells of OLK patients, whereas molecular biology studies revealed that low molecular weight fucoidan (LMWF) promoted apoptosis of dysplastic oral keratinocytes (DOK) and inhibited the growth and migration of DOK, and the inhibitory effect of LMWF on OLK was achieved by regulating the SR-A/Wnt signaling axis and related genes. Based on the above results and the special situation of the oral environment, we constructed LMWF/poly(caprolactone-co-lactide) nanofiber membranes with different structures for the in-situ treatment of OLK using electrospinning technology. The results showed that the nanofiber membranes with a shell-core structure had the best physicochemical properties, biocompatibility, and therapeutic effect, which optimized the LMWF drug delivery and ensured the effective concentration of the drug at the target point, thus achieving precise treatment of local lesions in the oral cavity. This has potential application value in inhibiting the development of OLK.